Evaluating the impact of physical frailty during ageing in wild chimpanzees (Pan troglodytes schweinfurthii). (9th November 2020) - Thompson, Melissa Emery; Machanda, Zarin P.; Fox, Stephanie A.; Sabbi, Kris H.; Otali, Emily; Thompson González, Nicole; Muller, Martin N.; Wrangham, Richard W.
Abstract : While declining physical performance is an expected consequence of ageing, human clinical research has placed increasing emphasis on physical frailty as a predictor of death and disability in the elderly. We examined non-invasive measures approximating frailty in a richly sampled longitudinal dataset on wild chimpanzees. Using urinary creatinine to assess lean body mass, we found moderate but significant declines in physical condition with age in both sexes. While older chimpanzees spent less of their day in the trees and feeding, they did not alter activity budgets with respect to travel or resting. There was little evidence that declining lean body mass had negative consequences independent of age. Old chimpanzees with poor lean body mass rested more often but did not otherwise differ in activity. Males, but not females, in poor condition were more likely to exhibit respiratory illness. Poor muscle mass was associated acutely with death in males, but it did not predict future mortality in either sex. While there may be some reasons to suspect biological differences in the susceptibility to frailty in chimpanzees versus humans, our data are consistent with recent reports from humans that lean, physically active individuals can successfully combat frailty. This article is part of the theme issue 'Evolution of the primate ageing process'.